Conflicts of interest - La Rosa Rodríguez, Emilio (Acta Bioethica, 2011)
This article reviews the concept of conflicts of interest with industry and the way these conflicts affect health care professionals work. Conflicts of interest of collective type in research, publications, writing good medical practice guidelines and with an increasing evidence, the relations of patients associations with industry are examined.